Participation of banks in small enterprise financing: problems and issues for Bangladesh - Hossain, Md Mosharref; Ibrahim, Yusnidah; Uddin, Md Mohan (2014)
The economic and social importance of the Small and Medium Enterprise (SME) sector nowadays is well acknowledged in academic and policy literature.SMEs play a very momentous role in the economy in terms of economic growth, employment creation, entrepreneur development and export earnings. Small enterprises lack access to finance due to their own constraints as well as the financial institutions’ perception of high risk and high cost.This paper attempts to find out the problems encountered by small enterprises in obtaining loans from banks in Bangladesh and the major problems faced by banks while financing small enterprises.For collecting primary data from the small businesses, three hundred forty one (341) small enterprises were interviewed through the questionnaires.Survey results show that 65.39% enterprises received loans from banks, while 34.61% enterprises did not receive any loan. Small enterprises face several problems in obtaining loan from banks.It is evident that high interest rate is the most significant problem followed by excessive security and guarantee requirement, working capital requirement, complexity of documentation, non availability of loan in due time, non availability of required amount, banker's reluctance and negligence, and mal-practices of bank officials.On the other hand, 22 different categories of banks are interviewed through the questionnaire.Banks cited different problems related to small enterprise financing of which non availability of required documentation, absence of good record of transactions, bad repayment history, lack of financial capacity, lack of security and guarantee are very common. Based on the study findings, a set of policy recommendations have been formulated.